Person centered coaching - Laneiro, Tito; Ribeiro, Luísa (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Executive coaching is a tool for professional development. Organizations want results, people want fulfillment and to perform. How much room should there be to accommodate both needs which we consider complementary? Coaching is inherently humanistic. However we find both theories and practices that do not truly respect this paradigm. The goal of this research is to test whether a new form of coaching following the Person Centered Approach (PCA) (i.e., humanistic), can promote personal and professional development. With this in mind, a PCA coaching training course was developed. The 13 participants (all white collar workers, mostly team managers) were asked to answer a trigger question. The resulting contents underwent a lexical analysis using Alceste software. Three classes were identified: the first relates to the course as a group cohesive force, promoting professional development, a second class resumes the value of the followed methodology, and a third one about skills and attitude development. We conclude that humanism and coaching can coexist, developing people in a holistic manner, making them aware of the several life dimensions – personal, organizational and social.